Optimal placement of capacitor banks in distorted electrical distribution network based on a constrained multi-objective immune algorithm - do Nascimento Alves, Helton (2016 IEEE Congress on Evolutionary Computation (CEC), 2016)
This paper presents a multi-objective algorithm for optimal placement of capacitor banks in distorted electrical distribution networks. A constrained multi-objective immune algorithm is proposed. The voltage profile constraints are used to define feasible solutions in the optimization process. Investments costs, power and energy losses costs and harmonic mitigation are considered in the solution. A 104-bus test system is presented and the results are compared to the solution given by a SPEA-II and a NSGA-II approach. The results confirm the efficiency of the proposed method which makes it promising to solve complex problems of planning in distribution feeders.